SnS2 quantum dots: facile synthesis, properties and applications in ultraviolet photodetector - Vincent Teng (Chinese Physics B, 2019)
Tin sulfide quantum dots (SnS2 QDs) are n-type wide band gap semiconductor. They exhibit a high optical absorption coefficient and strong photoconductive property in the ultraviolet and visible regions. Therefore, they have been found to have many potential applications, such as gas sensors, resistors, photodetectors, photocatalysts, and solar cells. However, the existing preparation methods for SnS2 QDs are complicated and require a high temperature and high pressure environment; hence they are unsuitable for large-scale industrial production. An effective method for the preparation of monodispersed SnS2 QDs at normal temperature and pressure will be discussed in this paper. The method is facile, green, and low-cost. In this work, the structure, morphology, optical, electrical, and photoelectric properties of SnS2 QDs are studied. The synthesized SnS2 QDs are homogeneous in size and exhibit good photoelectric performance. A photoelectric detector based on the SnS2 QDs is fabricated and its J-V and C-V characteristics are also studied. The detector responds under λ=365 nm light irradiation and reverse bias voltage. Its detectivity approximately stabilizes at 1011 Jones at room temperature. These results show the possible use of SnS2 QDs in photodetectors.